Narrative review on misoprostol for first trimester termination of pregnancy - Palani, Ramya Sadayandi; Gopalan, Ushadevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Misoprostol, a prostaglandin E1 analogue, is first used to prevent peptic ulcers. The first FDA-approved indication in the product labelling is for the prevention and treatment of intestinal ulcer disease caused by the use of nonsteroidal anti-inflammatory medications. The main advantages of misoprostol include it's reasonably priced, compared to other prostaglandins, it has modest effects on the smooth muscle of the heart and bronchial tree and is readily preserved (shelf life: 7 years) and it may be stored and used without refrigeration. Misoprostol has been authorised as an effective medication for termination of pregnancy at different gestations, cervical ripening, labour inducing in term pregnancy, and possibly therapy of postpartum haemorrhage in the last two decades.